The Role of ESG Activities in Strengthening Fan Trust and Loyalty: A Societal Perspective on Sustainable Sports Business - Dohun Kim; Yunduk Jeong (Societies)
This study aims to establish the impact of environmental, social, and governance (ESG) activities undertaken by South Korean professional sports clubs on fan trust and loyalty. Furthermore, it examines the moderating influence of fan citizenship among these connections. Data were gathered via surveys administered to 348 spectators at matches of two professional sports clubs in South Korea that are noted for their active ESG activities. Structural equation modeling (SEM) and moderation analysis using Jamovi software (version 2.4.8) were employed to analyze the data and test the proposed hypotheses. The findings reveal that environmental and social activities significantly impact fan trust and loyalty, whereas governance activities positively influence fan trust but do not significantly impact fan loyalty. Moreover, fan trust directly impacts fan loyalty. Regarding the moderating effects, fan citizenship strengthens the relationship between ESG activities and fan loyalty but does not affect the relationship between ESG activities and fan trust. This study contributes to this research by incorporating fan citizenship as a moderating variable in exploring how ESG practices can increase fan loyalty through fan citizenship. Moreover, these findings enhance our theoretical understanding by explaining how ESG strategies are related to relationship-building processes in the sports business, and they provide practical suggestions for teams on promoting sustainability and fan engagement by focusing on specific ESG activities.